Moral harassment in the workplace: An analysis of the impacts on work relationships - Bezerra, Edinalba Silva; Silva, Valderly Pereira da; Rego, Elson Jose do; Santos, Jane Karla de Oliveira (Seven Editora, 2023)
This study investigates the impacts of moral harassment in the workplace, focusing on the impacts and consequences generated both for the employee or collaborator, and for the organization in which they are inserted, as well as the legal effects arising from this illicit and inhumane practice, through A systematic literature review examines the physical, emotional and work-related effects caused to individuals who suffer moral harassment in the workplace, as well as the impacts on productivity and social engagement with co-workers. Understanding these impacts is essential to promoting a healthy work environment and mitigating the harmful effects of this conduct. DOI:https://doi.org/10.56238/sevened2023.006-054